Adaptabilidade e estabilidade de clones de cana-de-açúcar - Fernandes Júnior, Antonio Ribeiro [UNESP]; Andrade, João Antonio da Costa [UNESP]; Santos, Pedro César dos [UNESP]; Hoffmann, Hermann Paulo; Chapola, Roberto Giacomini; Carneiro, Monalisa Sampaio; Cursi, Danilo Eduardo (Instituto Agronômico de Campinas, 2013)
The objective of this study was to identify clones of sugarcane with good stability and adaptability in the State of São Paulo, Brazil, and also identifying locations most representative for selection and experimentation. Ten clones and two commercial checks of medium-late maturation were evaluated in the first-ratoon of experiments harvested in August 2009, using bissegmented regression and AMMI (Additive Main Effects and Multiplicative Interaction Analysis) methods. The results of two methods were compared and they evidenced that the clones RB975201, RB975157, RB975932, RB975242 and RB975162 are the most promising, showing higher production when compared to the checks, higher stability observed in one or both statistical methods and broader or more specific adaptability. The environment Tarumã presented higher stability and capacity to discriminate genotypes, allowing an ordering more reliable as compared to the overall mean of the environments tested.

O objetivo deste trabalho foi identificar clones de cana-de-açúcar produtivos, com boa estabilidade e adaptabilidade no estado de São Paulo e, também, identificar locais mais representativos para seleção e experimentação. Foram avaliados dez clones e duas testemunhas comerciais de maturação média-tardia em primeira soca de experimentos colhidos em agosto de 2009, utilizando o método de regressão bissegmentada e análise AMMI (Additive Main Effects and Multiplicative Interaction Analysis). Os resultados dos dois métodos foram comparados e evidenciaram que os clones RB975201, RB975157, RB975932, RB975242 e RB975162 foram os mais promissores devido à produtividade superior à das testemunhas, a alta estabilidade verificada em um ou nos dois métodos e a adaptabilidade ampla ou específica. O ambiente Tarumã apresentou maior estabilidade e capacidade de discriminação entre os genótipos, o que permite um ordenamento mais confiável em relação à média geral dos ambientes testados.
Adaptability and stability of sugarcane clones
Keywords: Saccharum spp.; interação genótipo x ambiente; regressão bissegmentada; AMMI; Saccharum spp.; genotype x environment interaction; bissegmented regression; AMMI